Population geography: Social justice for a sustainable world - Hazen, Helen D.; Alberts, Heike C.; Zaniewski, Kazimierz J. (London Routledge, 2024)
This book surveys the ways in which geographic approaches may be applied to population issues, exploring how human populations are embedded in natural and social environments. It encourages students to evaluate population issues critically, given that population topics are at the heart of many of today$1 (Bs most contentious subjects.s